2020
DOI: 10.3390/molecules25092196
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of Boronates Using VFFDT and Paramfit for Molecular Dynamics Simulation

Abstract: Boric acid, borate esters, and hydroxy derivatives are biologically active molecules. Thus, performing molecular dynamics simulations of these molecules is vital in terms of drug design, but it is difficult to find directly generated Amber parameters based on an ab initio method for these kinds of molecules in the literature. In this study, Amber parameters for such molecules containing boron were generated based on ab initio calculations using the paramfit program, which applies a combination of genetic and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The structure of Bovine Serum Albumin (BSA) was obtained from the Protein Data Bank (PDB ID: 4F5S, 2.47 Å). The structure of [B(Ph) 4 ] − (referred to as BPH for simplicity) was parameterized as by Kurt and Temel [38,39] and later built in xleap of AMBER16 package [40].…”
Section: Structuresmentioning
confidence: 99%
“…The structure of Bovine Serum Albumin (BSA) was obtained from the Protein Data Bank (PDB ID: 4F5S, 2.47 Å). The structure of [B(Ph) 4 ] − (referred to as BPH for simplicity) was parameterized as by Kurt and Temel [38,39] and later built in xleap of AMBER16 package [40].…”
Section: Structuresmentioning
confidence: 99%
“…The obtained results were then used with the selenoglycosides as follows. The SeDG ligands were indeed parametrized using Gaussian 09 [ 19 ] and VFFDT [ 20 , 21 ] and an MD simulation of the ligand alone (free state) was performed to evaluate the stability of the ligand and possible parametrization errors. The results highlighted that in the free state, two different families for the ligand were observed, which differed in their adoption of an extended and V-shaped conformation.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps this explains why there are not many examples of simulation studies involving ligands of this type. Herein, we have applied Seminario method ( Seminario, 1996 ) implemented in the Visual Force Field Derivation Toolkit (VFFDT) ( Zheng et al, 2016 ) and Paramfit programs recently reported ( Kurt and Temel, 2020 ). This approach was first validated by studying the QPX7728@OXA-48 enzyme complex for inactivation (Michaelis complex) and the subsequent QPX7728@OXA-48 enzyme adduct, and the latter was compared with the experimentally obtained (PDB ID 6V1O).…”
Section: Resultsmentioning
confidence: 99%
“…Boron parametrization was performed using the Seminario method ( Seminario, 1996 ) implemented in the VFFDT ( Zheng et al, 2016 ) and Paramfit programs ( Kurt and Temel, 2020 ). Usual GAFF atom types were applied to all atoms except for boron.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation